The stripping analysis of Hg(II) and Cu(II) based on hierarchical RTIL/γ-AlOOH/Fe(OH)3 composite. (10th October 2018) - Zhang, Yongxing; Wang, Qi; Xie, Fazhi; Xiong, Shiquan
Abstract: It is rather important to not only obtain the better detection efficiency for metal ions, but also investigate the change of sensitivity and detection limit in the simultaneous detection. Herein, a novel type of room temperature ion liquid (RTIL)/γ-AlOOH/Fe(OH)3 composite was prepared. Both the individual and simultaneous determination of Hg(II) and Cu(II) were examined by the composite electrode. The electrode exhibited the lowest limits of detection (LODs) of 0.5 and 0.3 nM for Hg(II) and Cu(II) in simultaneous determination, the highest sensitivities of 64.5 and 65.9 μA/μM, respectively, and the shortest response time. Both Hg(II) and Cu(II) films electroplated on the surface of composite were used to further analyze change of sensitivity and LOD, respectively. The thickness of films influenced the sensitivity and LOD. The proposed electrode was also performed the analysis of soil sample. The analytic method in this study could open up an avenue for the analysis and detection of metal ions, and provide a reference of electrochemical sensor based on metal films.